Prevention and treatment of high altitude pulmonary edema (HAPE) - Karol Mazur; Dominik Machaj; Sandra Jastrzębska; Alicja Płaczek; Dominika Mazur (Kazimierz Wielki University, 2020)
High-altitude pulmonary edema (HAPE) is a life-threatening form of non-cardiogenic pulmonary edema, that develops within the first 2-5 days in rapidly ascending individuals at altitudes above 2,500-3,000 m. The clinical features are cyanosis, tachypnoea,tachycardia and elevated body temperature generally not exceeding 38.5 °C. It is often severe and potentially fatal manifestation of acute mountain sickness (AMS). The aim of this study was to assess the methods of prevention and treatment of high altitude pulmonary edema (HAPE). Our study material consisted of publications, which were found in PubMed, ResearchGate and Google Scholar databases. The first step was to find proper publications from the last 30 years .The second step was to carry out an overview of the found publications. Gradual ascent and staged ascent are the most effective methods of prevention of HAPE Pharmacologic prophylaxis with nifedipine should only be considered for individuals with a history of HAPE.  Before initiating treatment of HAPE differential diagnosis should be done. Descent shoud be initaited and oxygen therapy shoud be started when HAPE is suspected or diagnosed. If these methods are unavailable, nifedipine or Gamow bag can be used.